Engineering particle morphology with microfluidic droplets. (16th June 2016) - Kang, Zhanxiao; Kong, Tiantian; Lei, Leyan; Zhu, Pingan; Tian, Xiaowei; Wang, Liqiu
Abstract: The controlled generation of microparticles with non-spherical features is of increasing importance. Such particles are useful for fundamental studies in areas such as self-assembly, as well as biomedical applications from drug carriers to photonic devices. We propose a simple model that captures the dominating factors controlling the size and morphology of non-spherical particles from phase separated droplets. The validity of our model is verified by comparing the generated non-spherical microparticles by droplet microfluidics. This simple relationship between the dominating factors and the final morphologies enables the production of non-spherical particles with well-defined shapes and tightly-controlled dimensions for a variety of applications from drug delivery vehicles to structural materials.